Automated landmarking for palatal shape analysis using geometric deep learning. (21st July 2021) - Croquet, Balder; Matthews, Harold; Mertens, Jules; Fan, Yi; Nauwelaers, Nele; Mahdi, Soha; Hoskens, Hanne; El Sergani, Ahmed; Xu, Tianmin; Vandermeulen, Dirk; Bronstein, Michael; Marazita, Mary; et al.
Abstract: Objectives: To develop and evaluate a geometric deep‐learning network to automatically place seven palatal landmarks on digitized maxillary dental casts. Settings and Sample Population: The sample comprised individuals with permanent dentition of various ethnicities. The network was trained from manual landmark annotations on 732 dental casts and evaluated on 104 dental casts. Materials and Methods: A geometric deep‐learning network was developed to hierarchically learn features from point‐clouds representing the 3D surface of each cast. These features predict the locations of seven palatal landmarks. Results: Repeat‐measurement reliability was <0.3 mm for all landmarks on all casts. Accuracy is promising. The proportion of test subjects with errors less than 2 mm was between 0.93 and 0.68, depending on the landmark. Unusually shaped and large palates generate the highest errors. There was no evidence for a difference in mean palatal shape estimated from manual compared to the automatic landmarking. The automatic landmarking reduces sample variation around the mean and reduces measurements of palatal size. Conclusions: The automatic landmarking method shows excellent repeatability and promising accuracy, which can streamline patient assessment and research studies. However, landmark indications should be subject to visual quality control.